(untitled) (American Journal of Islam and Society, 2005)
This book presents the thoughts of M. Fethullah Gülen, one of the world’s most influential Muslim scholars today. His ideas are attractive to many people because they give guidance on how to combine Islamic values with contemporary demands. Moreover, his emphasis on interfaith dialogue has earned him an international audience from various religious backgrounds. Thus, Gülen’s movement has spread rapidly throughout the world with schools, cultural and media activities, and dialogue projects. This book is a compilation of Gülen’s writings, interviews, and speeches that address such contemporary topics as interfaith dialogue, jihad, Sufism, and education. Moreover, it is among the first to address the timely issue of dialogue among civilizations. The book clearly presents Gülen’s understanding of such a dialogue as a deliberate undertaking based upon love, dialogue, and tolerance among people of different backgrounds. Readers who are not familiar with the context of these ideas in Turkish history, however, may find it difficult to follow the flow of some of his ideas. Gülen proposes dialogue for mutual enrichment and sharing as a solution to the “clash of civilizations” (p. 257), stating that the Abrahamic religions, especially Islam, are against disorder, treachery, conflict, and oppression (p. 256). His model is based on people dedicating their lives to thought and activism for the sake of God and creation. Both Muslims and non-Muslims can benefit from this book. The author reminds Muslims of Islam’s teachings on dialogue, using the Qur’an and the Hadith to show that tolerance, love, and compassion have been the main Islamic values throughout Islamic history and signify the importance of “reflecting God’s Mercy on themselves.” It may also help certain non- Muslims move beyond their prejudice, distrust, and misinformation and arrive at a deeper understanding of Islam. Gülen engages non-Muslims in ...